2015
DOI: 10.1136/annrheumdis-2015-207764
|View full text |Cite
|
Sign up to set email alerts
|

A randomised, double-blind, phase III study comparing SB2, an infliximab biosimilar, to the infliximab reference product Remicade in patients with moderate to severe rheumatoid arthritis despite methotrexate therapy

Abstract: ObjectivesTo compare the efficacy, safety, immunogenicity and pharmacokinetics (PK) of SB2 to the infliximab reference product (INF) in patients with moderate to severe rheumatoid arthritis (RA) despite methotrexate therapy.MethodsThis is a phase III, randomised, double-blind, multinational, multicentre parallel group study. Patients with moderate to severe RA despite methotrexate therapy were randomised in a 1:1 ratio to receive either SB2 or INF of 3 mg/kg. The primary end point was the American College of R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
151
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(159 citation statements)
references
References 27 publications
5
151
0
3
Order By: Relevance
“…IFX CT-P13 also demonstrated clinical efficacy in another RCT of MTX-IR RA 46. Efficacy was also formally proven in placebo-controlled RCTs with the ADA bsDMARDs ABP50147 and SB5,48 with the ETN bsDMARDs HD20349 and SB4,50 with the IFX bsDMARD SB251 and with the RTX bsDMARD BCD-020 52…”
Section: Resultsmentioning
confidence: 89%
“…IFX CT-P13 also demonstrated clinical efficacy in another RCT of MTX-IR RA 46. Efficacy was also formally proven in placebo-controlled RCTs with the ADA bsDMARDs ABP50147 and SB5,48 with the ETN bsDMARDs HD20349 and SB4,50 with the IFX bsDMARD SB251 and with the RTX bsDMARD BCD-020 52…”
Section: Resultsmentioning
confidence: 89%
“…1): screening, treatment period 1 (weeks 0-12), treatment period 2 (weeks [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] and an extension phase (weeks 31-52). In treatment period 1, patients were randomized 1 : 1 to self-administer 50 mg GP2015 or 50 mg ETN (Enbrel â ; Amgen Inc., Thousand Oaks, CA, U.S.A.; European Union authorized) twice weekly, subcutaneously.…”
Section: Methodsmentioning
confidence: 99%
“…17,18 Other biosimilar studies have also reported higher response rates for the primary efficacy parameter compared with the pivotal studies for the originator product. 21,[26][27][28] Moreover, the EGALITY study was designed to establish similarity between GP2015 and ETN …”
Section: -22mentioning
confidence: 99%
“…Thus far, comparative studies between infliximab original and biosimilars as well as between etanercept original and biosimilars have revealed no significant differences in efficacy and safety. This also includes randomized trials on switching from the original to the biosimilar [11,12,13]. Importantly, the rate of induced antibodies against the biopharmaceutical did not differ.…”
Section: Efficacy Safety and Benefitmentioning
confidence: 99%